1998
DOI: 10.1063/1.367925
|View full text |Cite
|
Sign up to set email alerts
|

The influence of field- and stress-induced magnetic anisotropy on the magnetoimpedance in nanocrystalline FeCuNbSiB alloys

Abstract: The correlation between magnetic anisotropy and magnetoimpedance has been studied in field- and stress-annealed Fe73.5Cu1Nb3Si13.5B9 ribbons. As-cast and previously nanocrystallized samples were submitted to different annealing conditions (T=500, 530, and 560 °C and tensile stress σ=150 MPa) in order to induce different magnetic anisotropy. The magnetoimpedance ratio [ΔZ/Z] was measured at 3 MHz using a driving current Irms=10 mA. An hysteretic behavior of the magnetoimpedance ratio is observed. This hystereti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Similar peak phenomenon was observed in the uniform wires, ribbons and films, which was attributed to the existence of circumferential or transverse anisotropy and the permeability peak around anisotropy field H K (H K % H P ). [3][4][5][6][7][8] It has been found that in the electrodeposited CoP film there is a transition of magnetic anisotropy with regards to the thickness D of CoP: For D < 0:4 mm, the anisotropy is planar. For 0:4 mm < D < 10 mm it is an oblique anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar peak phenomenon was observed in the uniform wires, ribbons and films, which was attributed to the existence of circumferential or transverse anisotropy and the permeability peak around anisotropy field H K (H K % H P ). [3][4][5][6][7][8] It has been found that in the electrodeposited CoP film there is a transition of magnetic anisotropy with regards to the thickness D of CoP: For D < 0:4 mm, the anisotropy is planar. For 0:4 mm < D < 10 mm it is an oblique anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…1,2) The GMI effect consists in a magnetic field induced changes in the complex impedance due to the variation of magnetic permeability. Besides of the uniform wires, ribbons and films, [3][4][5][6][7][8] this effect has been observed in inhomogeneous structured materials such as non -magnetic conducting wire plated with magnetic layers and some sandwich films. [9][10][11][12][13][14][15][16][17][18] Large GMI effect occurs at a relative low frequency in BeCu/NiFe, 9) BeCu/CoFeNi, 10) Ag/NiFe 11) and Cu/CoP 12,13) plated wires.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Early works on the MI effect are on the nearly non-magnetostrictive FeCoSiB amorphous wires. [4][5][6] The investigation on the MI effect have been quickly extended to amorphous FeCoSiB ribbons 5,7) and Fe based nanocrystalline ribbons/wires such as FeCuNbSiB, [8][9][10] FeZrB 11,12) and permalloy ribbons/wires NiFeMo. 13,14) In the present work, we report the magnetoimpedance effect in the as cast ribbon Nd 4 Fe 77.5 B 18.5 with melt-spun quenching speed of 40 m/s.…”
Section: )mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] The MI effect includes a sensitive change in impedance with the application of a small DC magnetic field. It was suggested that the MI effect strongly depends on the variation in skin depth via the permeability.…”
Section: )mentioning
confidence: 99%
“…9 Except for varying the composition and geometric structure of the materials, many studies employed field or stress annealing to induce circumferential/transverse magnetic domain structure. 10,11 The most commonly used fabrication methods for composite wires, such as RF sputtering, 20 electroplating 17, 21 and chemical plating, 22,23 cannot control well the magnetic structure. Recently, we imposed a DC current during the process of the chemical plating, and it can significantly improve the GMI effect of composite wire.…”
Section: Introductionmentioning
confidence: 99%